2009
DOI: 10.1016/j.ijdevneu.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

ZnCl2 exposure protects against behavioral and acetylcholinesterase changes induced by HgCl2

Abstract: This study examined the effects of inorganic mercury exposure on behavioral and biochemical parameters and investigated the possible preventive effects of zinc on the alterations induced by mercury. Pups were exposed from 3rd to 7th postnatal day to ZnCl2 (27 mg/kg/day, s.c.) and subsequently to HgCl2 (5 doses of 5 mg/kg/day, s.c.). Each litter contained two rats for each treatment. The rats were submitted to behavioral task and litters were killed at 13 or 33 days old for acetylcholinesterase activity assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…Inorganic mercury also affects liver, blood, intestine, thyroid and testicles [3,4]. In fact, recent studies have demonstrated that animals exposed to mercury chloride (HgCl 2 ) (5 mg/kg) present renal [5][6][7][8], hepatic [9][10][11][12], testicular [13], behavioral [14,15] and cardiovascular [16] alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic mercury also affects liver, blood, intestine, thyroid and testicles [3,4]. In fact, recent studies have demonstrated that animals exposed to mercury chloride (HgCl 2 ) (5 mg/kg) present renal [5][6][7][8], hepatic [9][10][11][12], testicular [13], behavioral [14,15] and cardiovascular [16] alterations.…”
Section: Introductionmentioning
confidence: 99%
“…The dose of HgCl 2 was selected according to previous studies performed with suckling rats, which demonstrated several biochemical and physiological damages induced by this dose [4][5][6]11,15,17]. From 8 to 12 days old they received one daily dose of saline or HgCl 2 5 mg/kg/day (3.7 mg/kg/day of Hg).…”
Section: Copper and Mercury Exposurementioning
confidence: 99%
“…Its toxicity depends on the chemical form in which the exposure occurs [1,2]. However, several studies have related other toxic effects induced by the inorganic form of mercury, such as (1) changes in body and organ weight [5,6], (2) hematological and immunological alterations [7], (3) inhibition of porphobilinogen synthase (PBG-synthase) activity of different tissues in vivo [5,6,[8][9][10] and in vitro [8,9], (4) inhibition of cerebellum acetylcholinesterase [11], and (5) serum alanineaminotransferase (ALT) activities, and (6) increase of serum creatinine and urea levels [4,5]. However, several studies have related other toxic effects induced by the inorganic form of mercury, such as (1) changes in body and organ weight [5,6], (2) hematological and immunological alterations [7], (3) inhibition of porphobilinogen synthase (PBG-synthase) activity of different tissues in vivo [5,6,[8][9][10] and in vitro [8,9], (4) inhibition of cerebellum acetylcholinesterase [11], and (5) serum alanineaminotransferase (ALT) activities, and (6) increase of serum creatinine and urea levels [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic mercury (HgCl 2 ) is primarily nephrotoxic ; however, its effect on CNS during early periods of development is well documented. In fact, we recently demonstrated that HgCl 2 induces behavioral impairment and accumulation of this metal in the cerebrum and cerebellum .…”
Section: Introductionmentioning
confidence: 98%